On-demand zero-drag hydrodynamic cloaks resolve D'Alembert paradox in viscous potential flows - Neng-Zhi Yao; Bin Wang; Hao Wang; Chen-Long Wu; Tien-Mo Shih; Xuesheng Wang (Microsystems & Nanoengineering)
Abstract The possibility of freely manipulating flow in accordance with humans will remain indispensable for breakthroughs in fields such as microfluidics, nanoengineering, and biomedicines, as well as for realizing zero-drag hydrodynamics, which is essential for alleviating the global energy crisis. However, persistent challenges arise from the D’Alembert paradox and the unresolved Navier-Stokes solutions, known as the Millennium Problem. These obstacles also complicate the development of hydrodynamic zero-drag cloaks across diverse Reynolds numbers. Our research introduces a paradigm for such cloaks, relying exclusively on isotropic and homogeneous viscosity. Through experimental and numerical validations, our cloaks exhibit zero-drag properties, effectively resolving the D’Alembert paradox in viscous potential flows. Moreover, they possess the capability to activate or deactivate hydrodynamic concealment at will. Our analysis emphasizes the critical role of vorticity manipulation in realizing cloaking effects and drag-reduction technology. Therefore, controlling vorticity emerges as a pivotal aspect for future active hydrodynamic zero-drag cloak designs. In conclusion, our study challenges the prevailing belief in the impossibility of zero drag, offering valuable insights into invisibility characteristics in fluid mechanics with implications for microfluidics, biofluidics demanding the drug release or biomolecules transportation accurately and timely, and hypervelocity technologies.